The Common Practices of Traditional Medicine in Afghanistan and the Related Challenges - Ayoubi, Rabia (Journal of Natural Sciences – Kabul University)
Traditional Afghan Medicine (TAM) remains widely practiced, with many people relying on it for managing and treating health conditions. However, there is insufficient and inconsistent information available about its common practices. This article presents a narrative review of the prevalent methods of TAM and some of the challenges associated with them. The findings of this study outline the common methods of traditional medicine in the country and may pave the way for their advancement and standardization. Fractional therapy, phytotherapy, fasd, cupping, hirudotherapy, enema, hydrotherapy, cauterization, massage therapy, acupuncture and spiritual and religious therapy are the common practices in TAM. Although the effectiveness and efficiency of these practices have been proven by scientific-experimental studies, still, the lack of a distinct procedure and national standard of traditional medicine has caused TAM to be used only within the country.